Development Of A Booklet On Cell Bioprocess Materials As A Supplement To Biology Teaching Materials For Class XI SMA/MA - Rahmi Ridhayani; S Syamsurizal (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2021)
Education has a broad meaning and an important role. One of the efforts teachers can make to improve education is to use a good and proper medium of study so that learners can readily understand biological material. The study aims to develop a learning medium of antibiotics that can serve as a supplement to the bioprocess of cells. The study uses a 4-D model of development limited to three stages define, design, and development. Research data is qualitative and quantitative. Validation results obtained a valiance value of 85.33% with very valid criteria. The result of the learner's response test is 82.19% with very positive criteria and the teacher's response test is an average of 90.34% with very positive criteria. It may thus be concluded that the compounds developed are so valid and so practical as to merit their use as a visual supplement.